Digital Parenting Practices and The Development of Social-Emotional Character In Early Childhood: A Case Study At Wahyu Kindergarten - Nurjannah Nurjannah; Anggi Wulandari; Risnawati Rasyid; Nuraisah Nuraisah; Hajerah Hajerah (Ihya Ulum: Early Childhood Education Journal, 2026)
The use of digital media by young children without parental supervision has been widely examined through quantitative approaches. However, qualitative research exploring how family digital parenting practices and teachers' roles jointly shape young children's social-emotional character within a small-scale early childhood education setting remains limited, particularly in the Indonesian context. This study addresses this gap by examining how parental digital parenting practices and teachers' roles collaboratively contribute to the development of children's social-emotional character at Wahyu Kindergarten. A qualitative case study design was employed, involving twelve purposively selected participants comprising one principal, three teachers, and eight parents. Data were collected through participant observation, semi-structured interviews, and document analysis, and were analyzed using data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source and methodological triangulation. The findings indicate that unsupervised digital device use is associated with reduced face-to-face social interaction, weakened self-discipline, and increased individualistic tendencies among young children. In contrast, communicative digital parenting accompanied by active parental guidance supports the development of responsibility, politeness, and social skills. These positive outcomes are further reinforced by teachers through behavioral modeling and the facilitation of positive peer interactions within the school environment. Theoretically, this study contributes a collaborative framework for parents and teachers to promote balanced digital parenting practices that support the development of young children's social-emotional character in early childhood education settings.